IMPLEMENTATION OF INTERGRATED ASSESSMENT AS A MEASURE TO ANTICIPATE OVERCAPACITY IN CORRECTIONAL INSTITUTIONS - bimantoro, satria; Sri Riski (Progressive Law Review, 2024)
Narcotics Crime Continues to be a Major Issue in Law Enforcement in Indonesia, Now Facing a Significant Surge in the Trafficking of Illegal Narcotics. The development of handling narcotics cases now involves integrated assessments aimed at providing rehabilitation for users, rather than solely imposing criminal sanctions. Correctional Institutions (Lapas) are also facing overcapacity issues due to the surge in narcotics-related cases. This study aims to identify the effectiveness of the implementation of integrated assessments in addressing overcapacity in Correctional Institutions. Using a mixed-methods approach, this research evaluates the effectiveness of integrated assessments in mitigating overcapacity in correctional institutions caused by the rise in narcotics cases in Indonesia. The qualitative method involves in-depth interviews, focus group discussions, and case studies for practical evaluations. The quantitative approach includes surveys and statistical data analysis regarding perceptions and conditions of overcapacity. The integration of results from both methods is expected to provide a comprehensive overview, identify challenges, and formulate strategic steps to improve the law enforcement and rehabilitation system.This study assesses the implementation of integrated assessments in addressing overcapacity in correctional institutions resulting from the surge in narcotics cases in Indonesia. Narcotic addiction, which is progressive and prone to relapse, requires medical and social rehabilitation. The integrated assessment, involving both medical and legal teams, aims to determine rehabilitation needs. The findings show that integrated assessments can reduce overcapacity by offering risk evaluations, alternative sentencing, and more effective rehabilitation programs. Furthermore, increasing correctional facility capacity, regular monitoring, and stakeholder engagement are necessary for long-term solutions.